Redescription of the tadpole of Leptodactylus natalensis Lutz (Anura: Leptodactylidae), an inhabitant of the Brazilian Atlantic Forest - Dubeux, Marcos J. M.; Da Silva, Thais D.; Mott, Tamí; Do Nascimento, Filipe A. C. (Zootaxa, 2020)
The Neotropical foam-nesting genus Leptodactylus Fitzinger is currently composed of 75 species (Frost 2019) divided into four monophyletic species groups (De Sá et al. 2014). The L. melanonotus species group includes 17 species delimited by five adult osteological character-states (De Sá et al. 2014). Leptodactylus natalensis Lutz is the only species of the L. melanonotus species group that occurs in north of the Brazilian Atlantic Rain Forest (De Sá et al. 2014; Almeida et al. 2016) and whose type locality is the municipality of Natal, state of Rio Grande do Norte, Brazil (Lutz 1930). The tadpole of this species was briefly described by Oliveira & Lírio-Júnior (2000) based on a single individual from the municipality of Aracaju, state of Sergipe, Brazil. Herein, we present a complete redescription of the tadpole of this species, including morphometric data and interpopulational variation. Besides, we provide comparisons with all members of the L. melanonotus group.